Visitor experiences: art, architecture and space at the papal curia c.1200. Issue 3 (27th May 2018) - Fonnesberg-Schmidt, Iben
ABSTRACT: The Lateran Palace in Rome was the main papal residence and the administrative centre of the papacy in the central Middle Ages. The physical setting that confronted visitors to the Roman curia at the Lateran Palace during the pontificate of Innocent III (1198–1216) can be explored by piecing together information from curial material and the few visitors' accounts about the architecture, art and use of space within this no-longer existent building. The article examines how visitors perceived the palace and the use of space within it, placing particular emphasis on visitors' admission to the different areas of the palace which determined their access to the pope and other members of the curia. The ways in which the layout and decoration of the palace reflected and reinforced notions of papal authority are also discussed.